Implementasi Kebijakan Kurikulum Merdeka di SMA Negeri 10 Semarang - Sephani, Sabrina Gendis Midya; Gustaman, Fulia Aji (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The independent curriculum designed by the Ministry of Education and Culture, namely Nadiem Makarim, encourages active participation of students in the learning process, prioritizing project-based learning, real experiences, and the application of knowledge in the context of everyday life. This concept is rooted in the philosophy of Ki Hadjar Dewantara, a pioneer of national education. He argued that to realize an effective learning process, mature learning planning is needed. In order for learning objectives to be achieved, several important elements must be met, namely students, educators, clear learning objectives, relevant learning principles, and appropriate learning methods. This research method is qualitative, namely digging up information from various sources, namely stakeholders of SMA Negeri 10 Semarang. Based on the results of the study, it was found that the implementation of the independent curriculum policy at SMA Negeri 10 Semarang has been ongoing since the 2022 academic year. In terms of human resource readiness (teachers), preparation of learning tools, facilities and infrastructure, and implementation of P5 have been carried out optimally. Supporting factors in the implementation of the independent curriculum policy include the number of training and applications that can be easily copied and adapted by teachers to school conditions, in addition to the inhibiting factors are inadequate internet access and old computers and senior teachers who are not tech-savvy.